Motilitas spermatozoa manusia setelah simpan beku dengan medium TES-Tris yolk citrat (TES-TYC) - Djaelani, Muhammad Anwar; Sitasiwi, Agung Janika (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
The aim of this research was to evaluate the effect of semencryopreservation using TES-Tris yolk citrat (TES-TYC) medium onmotility of the sperm. Semen fulfilling inclusion criteria with WHO 1999 criteria. The sperm motility was counted as initial data. The semen was then mixed with TES-TYC medium and cryopreserved in liquid nitrogen. After one mounth the semen was thawed and recount its sperm motility. Data obtained showed that the motility of post freezing sperm cryopreserved was lower compared to the motility of pre freezing sperm. It could be concluded that cryopreservation caused decrease integrity and death of sperm during cryopreservation, that showed the motility of post freezing sperm cryopreserved was lower compared to the motility of prefreezing sperm.